The potential for small enterprise to consider guerrilla marketing from brand equity perspective - Nguyen, Vu Tu Phuong (2020)
The innovation of society entails consumers’ demand. It is not only product quality but also brand image. In particular, it requires the organization to be active in their marketing updates in order to enhance the brand value. In addition, after discussing with the case company, the topic arose as a development project to advance the marketing tactics for brand equity. Thus, this thesis topic concentrated on new marketing, guerrilla marketing, and the relation to brand equity. After finding the relation, the writer’s responsibility was to research if the company case has the potential to execute guerrilla marketing as a renovative project in a niche market. The literature section started with brand equity in two areas of the consumers’ side, which were brand awareness and perceived quality. It showed the connection of the organization’s image on consumers with the value of branding. The theory continued with guerrilla marketing and focused on its characteristics. The main point was to discover the connection attributes between brand equity and guerrilla marketing to set the criteria for the case company, Taiga Chocolate, before launching the guerrilla campaign. In terms of the empirical case, the study was conducted by interview one-by-one. The respondents’ answers to determine the ability of the company achieved the set criteria. The internal and external employees gave different points of view to ensure validity and reliability. The study findings were if Taiga Chocolate could reach the criteria to be able to execute guerrilla marketing in the Hongkong market. The result gathered the influence of guerrilla marketing tactics to the brand image. In addition, the result was the beginning of the development project. Therefore, more time is needed to receive reliable results guerrilla marketing in brand equity.